Phenyl rings mesogenic core of azo-ester based liquid crystals: Synthesis, mesomorphic and optical properties / Salwa Jamal M Kamal - Salwa , Jamal M Kamal (2022)
Azo-ester compounds containing two and three-benzene-ring in the mesogen bearing varied lateral substituent at the 2-position to the azo linkage including the laterally unsubstituted compounds, i.e. -H, -F and -CH3 with different terminal groups have been designed and synthesized. The chemical structures of all compounds were confirmed by Fourier transform infrared (FT-IR), 1H and 13C nuclear magnetic resonance (NMR) spectroscopy and elemental analysis. All resulting compounds exhibited good thermal stability (above 319℃), as confirmed by thermogravimetric analysis (TGA). The mesomorphic behaviours of liquid crystal compounds were studied by differential scanning calorimetry (DSC), polarized optical microscopy (POM) and small- and wide-angle X-ray scattering (SWAXS). Mesomorphic studies revealed that all derivatives were liquid crystalline materials except for the two-benzene-ring compounds (T1, T2 and T3) and the unsubstituted terminal three-benzene-ring analogues (S1, C1 and C6). The introduction of terminal electron-donating groups in the laterally unsubstituted derivatives (S2 and S3) gave nematic phase at 124°C and 135°C with marble and Schlieren textures, respectively. The laterally fluorinated azo-esters with terminal electron-donating groups (C2 and C3) exhibited nematic phase at 95°C and 117°C, respectively. The incorporation of terminal electron-withdrawing bromine atom in the laterally neat compound (S4) induced enantiotropic nematic-nematic phase transition, while the laterally fluorinated azo-ester analogue (C4) showed nematic-nematic phase transition upon cooling only. The terminal nitro group in both laterally neat and laterally fluorinated derivatives (S5 and C5) displayed nematic phase with clearing temperatures of 168°C and 164°C, respectively. The laterally methyl substituted compound with terminal electron-donating groups (C7 and C8) showed nematic mesophase temperatures at 105°C and 107°C, respectively, which are lower in values compared to the laterally neat and fluorinated analogues. SWAXS analysis confirmed the mesophase textures observed from POM. The absorption maxima of UV-Vis and photoluminescence spectra were influenced by the lateral and terminal substituents. The laterally methyl compounds showed blue-emission with a relatively higher fluorescence intensity compared to the lateral unsubstituted and fluorinated derivatives.